The Principle of Gratuitousness: Opportunities and Challenges for Business in «Caritas in Veritate» - McCann, Dennis 1945- (2011)
One major theme in Pope Benedict XVI’s encyclical Caritas in Veritate is the “Principle of Gratuitousness.” The point of this essay is to begin a reflection on what it actually means and its possible relevance. By comparing the “Principle of Gratuitousness” and its normative assumptions about “the logic of gift” with anthropological studies focused on the same phenomenon, I hope to show, not only the relevance of the encyclical’s normative vision but also where and how it needs further clarification. The findings of empirical anthropology provide qualified support for the encyclical’s focus on generating and replenishing “social capital” in order to sustain both markets and politics in an effort to “civilize the economy.” In order to put the “Principle of Gratuitousness” into more effective practice, the encyclical highlights the creative role of “civil society” and calls for the creation social enterprises whose goals are broader and deeper than maximizing profits. Assessing the realism of Benedict’s proposal will require further research and reflection on innovative entrepreneurial ventures designed to address social problems on a commercial basis, for example, Muhammad Yunus’ concept of a “social business” and its development in a series of joint business ventures involving the Grameen Bank and related organizations.
Keywords: Caritas in Veritate; Muhammad Yunus; Benedict XVI; Catholic Social Teaching; Intrinsic and instrumental motivation in business; Social business; Social Capital; The logic of gift exchanges; Reciprocity; Gratuitousness